Regulation of Hematopoietic Cell Development and Function Through Phosphoinositides - Elich, Mila; Sauer, Karsten (Frontiers in Immunology, 2018)
One of the most paramount receptor-induced signal transduction mechanisms in hematopoietic cells is production of the lipid second messenger phosphatidylinositol(3,4,5)trisphosphate (PIP3) by class I phosphoinositide 3-kinases (PI3K). Defective PIP3 signaling impairs almost every aspect of hematopoiesis, including T cell development and function. Limiting PIP3 signaling is particularly important, because excessive PIP3 function in lymphocytes can transform them and cause blood cancers. Here, we review the key functions of PIP3 and related phosphoinositides in hematopoietic cells, with a special focus on those mechanisms dampening PIP3 production, turnover or function. Recent studies have shown that beyond "canonical" turnover by the PIP3 phosphatases and tumor suppressors PTEN and SHIP1/2, PIP3 function in hematopoietic cells can also be dampened through antagonism with the soluble PIP3 analogs inositol(1,3,4,5)tetrakisphosphate (IP4) and inositol-heptakisphosphate (IP7). Other evidence suggests that IP4 can promote PIP3 function in thymocytes. Moreover, IP4 or the kinases producing it limit store-operated Ca2+ entry through Orai channels in B cells, T cells and neutrophils to control cell survival and function. We discuss current models for how soluble inositol phosphates can have such diverse functions, and can govern as distinct processes as hematopoietic stem cell homeostasis, neutrophil and NK cell function, and development and function of B cells and T cells. Concluding, we will review the pathological consequences of dysregulated IP4 activity in lymphocytes, and highlight contributions of impaired inositol phosphate functions in disorders such as Kawasaki disease, severe combined immunodeficiency or blood cancer.